Federal Justice Statistics Program: Arrests and Bookings for Federal Offenses, 2021 ([Verlag nicht ermittelbar], 2023)
The data contain records of arrests and bookings for federal offenses in the United States during fiscal year 2021. The data were constructed from the United States Marshals Service (USMS) Capture database. Records include arrests and bookings made by federal law enforcement agencies (including the USMS) and state and local agencies. Justice involved individuals arrested or booked for federal offenses are transferred to the custody of the USMS for processing, transportation, and detention. The Capture system contains data on all justice involved individuals within the custody of the USMS. Variables containing identifying information were either removed, coarsened, or blanked in order to protect the identities of individuals. A primary difference between the 2020 data and previous years is that the 2020 data were subset based upon an admission to custody in the fiscal year. In previous years, arrest date was used to subset the records. Some individuals in the 2021 data will have a missing arrest date. These data are part of a series designed by Abt Associates and the Bureau of Justice Statistics. Data and documentation were prepared by Abt Associates.